2021
DOI: 10.3390/ma14185367
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Technology and Properties of Fe/TaC Metal Matrix Composite Coatings Produced on Medium Carbon Steel Using Laser Processing—Preliminary Study on the Single Laser Tracks

Abstract: The paper presents study results of Fe/TaC metal matrix composite coatings produced on tool steel using laser processing of TaC pre-coat. The Fe/TaC coatings were produced in two steps. First, a pre-coat in the form of a paste based on tantalum carbide and water glass was made and then applied to the steel substrate. In the second step, the TaC pre-coat was remelted with steel substrate using a diode laser beam with a rated power of 3 kW. A constant scanning speed of the laser beam of 3 m/min and three types o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…It is true that a new structure will be obtained, in which the dendritic precipitates and matrix can be identified. However, such a structure cannot be treated as a composite structure, where the phases are clearly separated from each other, as was obtained in previous studies on other types of carbides [ 10 , 11 , 17 ]. However, it can be concluded that the use of both the W-Cr matrix and the Cr 3 C 2 reinforcing phase has a significant impact on building a new structure, and that the careful selection of the laser beam parameters can control the shape of the individual structural elements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is true that a new structure will be obtained, in which the dendritic precipitates and matrix can be identified. However, such a structure cannot be treated as a composite structure, where the phases are clearly separated from each other, as was obtained in previous studies on other types of carbides [ 10 , 11 , 17 ]. However, it can be concluded that the use of both the W-Cr matrix and the Cr 3 C 2 reinforcing phase has a significant impact on building a new structure, and that the careful selection of the laser beam parameters can control the shape of the individual structural elements.…”
Section: Resultsmentioning
confidence: 99%
“…Among galvanic methods, the most common, such as nickel plating, chromium plating or zinc plating, can be distinguished. The methods that are gaining recognition and being more frequently developed and described by researchers are high-energy techniques, such as laser cladding [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ], plasma arc cladding [ 14 , 15 ] and laser alloying [ 16 , 17 ]. These methods are increasingly used in industry.…”
Section: Introductionmentioning
confidence: 99%
“…The laser is used both in the processing of metallic and non-metallic materials. The use of the laser beam for the production of coatings on ferrous (steel, cast iron) [6][7][8][9][10][11][12][13][14] and non-ferrous alloys (mainly nickel and cobalt alloys) [15][16][17][18] is particularly interesting. Recently, laser surface modification techniques have become quite widespread in industrial applications [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…Much less attention is given to other types of carbides. Tantalum carbide [12,15,[37][38][39][40] and zirconium carbide [41][42][43][44] seem to be very interesting. A mixture of these two carbides forms one of cermets, i.e., ceramic-metal sinters, characterized by very high hardness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation